A feasibility study of geogenic indoor radon mapping from airborne radiometric survey in northern Thailand - Wattananikorn K. (2014)
Experiments were carried out in seven test sites on three Quaternary alluvial and terrace deposit basins of northern Thailand, to test the possibility of using airborne equivalent uranium to predict geogenic indoor radon values of the region. The methodology was based on the correlation among soil gas permeability, soil radon concentration and indoor radon, as well as a relationship between soil radon and airborne uranium values. The methodology established works rather well when tested in areas of known indoor radon. Based on the predicted values that were obtained from this method, indoor radon in most areas of alluvial and terrace deposit basins of northern Thailand is less than 44 Bq / m3. There is no area in these basins where predicted indoor radon exceeds 74 Bq / m3. © 2007 Elsevier Ltd. All rights reserved.